Gambaran tingkat kecemasan dengan pengukuran TMAS dan prestasi belajar siswa perempuan dan laki-laki kelas 1 SMA Negeri 1 Kawangkoan - Mamuaya, Miracle H.; Elim, Christofel; Kandou, Lisbeth F.J. (e-CliniC, 2016)
Abstract: Anxiety arises as a result of the response to stress or conflicts. This is commonly occurs when a person experiences any changes in his/her life and is required to be able to adapt. Anxiety is the most common mental disorders. Around 20% of the world population suffers from anxiety and as many as 47.7% of teenagers often feel anxious. High school students are prone to anxiety. Psychosocial stressor is any situation that causes a change in one's life so that he/she is forced to adapt or cope with stressors that arise. Changes in the learning environment has also become one of the trigger factors of anxiety and depression in high school students. This study aimed to obtain the difference of the degrees of anxiety and depression between high school male students and female students. This was a descriptive analytical study with a cross sectional design. All respondents’ achievement and levels of anxiety obtained from TMAS questionnaires were noted. In this study there were 144 selected respondents consisted of 74 female students and 70 male students; all were grade 1 students. The results showed that most male students did not experience anxiety (43 students; 61.42%). On the contrary, most female students experienced anxiety (57 students; 77.02%). Among the male students, most of them who did not experience anxiety had an average value between 80-90 meanwhile among the female students most of them who experienced anxiety had a value achievement of 80-90. Conclusion: There was no relationship between the level of anxiety and value of achievement among high school students in Kawangkoan. Keywords: homeostasis, psychosocial stressors, distorted perception. Abstrak: Kecemasan timbul akibat adanya respon terhadap kondisi stres atau konflik. Hal ini biasa terjadi bila seseorang mengalami perubahan situasi dalam hidupnya dan dituntut untuk mampu beradaptasi. Kecemasan merupakan gangguan mental terbesar. Diperkirakan 20% dari populasi dunia menderita kecemasan dan sebanyak 47,7% remaja sering merasa cemas. Siswa SMU rentan terhadap kecemasan. Stresor psikososial adalah setiap keadaan yang menyebabkan perubahan dalam kehidupan seseorang sehingga orang itu terpaksa beradaptasi atau menanggulangi stresor yang timbul. Perubahan lingkungan belajar juga menjadi salah satu faktor pencetus kecemasan dan depresi pada siswa SMU. Penelitian ini bertujuan untuk mengetahui perbedaan derajat kecemasan dan depresi antara siswa SMU laki-laki dan perempuan kelas 1 SMA Negeri 1 Kawangkoan. Jenis penelitian ini deskriptif analitik dengan desain potong lintang. Dari keseluruhan responden gambaran yang diamati meliputi nilai capaian siswa dan tingkat kecemasan yang diperoleh dari kuesioner TMAS. Dari hasil penelitian diperoleh 144 responden yang terdiri dari 74 siswa perempuan dan 70 siswa laki-laki dari siswa kelas 1. Sebagian besar remaja laki-laki tidak mengalami kecemasan yakni sebanyak 43 siswa (61,42%) sedangkan pada siswa perempuan sebagian besar mengalami kecemasan yakni sebanyak 57 siswa (77,02%). Pada remaja laki-laki jumlah terbanyak siswa Mamuaya, Elim, Kandouw: Gambaran antara tingkat... yang tidak mengalami kecemasan memiliki nilai rata-rata antara 80-90. sedangkan pada remaja perempuan yang memiliki jumlah kecemasan tertinggi berada pada nilai capaian 8 . Simpulan: Tidak ditemukan hubungan antara tingkat kecemasan dan nilai capaian studi pada siswa SMU kelas 1 SMA Negeri 1 Kawangkoan. Kata kunci: homeostasis, stresorpsikososial, distorsipersepsi